Next year in Havana [compact disc unabridged] - Cleeton, Chanel (Blackstone Publishing, 2018)
Arriving in Havana, Marisol comes face-to-face with the contrast of Cuba's tropical, timeless beauty and its perilous political climate. When family history comes to light and Marisol finds herself attracted to a man with secrets of his own, she'll need the lessons of her grandmother's past to help her understand the true meaning of courage.